Morrey spaces : introduction and applications to integral operators and PDE's. Volumes I & II - Sawano, Yoshihiro; Di Fazio, Giuseppe, 1963-; Hakim, Denny Ivanal (Boca Raton : Chapman & Hall/CRC, 2020)
Morrey spaces were introduced by Charles Morrey to investigate the local behaviour of solutions to second order elliptic partial dierential equations. The technique is very useful in many areas in mathematics, in particular in harmonic analysis, potential theory, partial dierential equations and mathematical physics. Across two volumes, the authors of Morrey Spaces: Introduction and Applications to Integral Operators and PDE's discuss the current state of art and perspectives of developments of this theory of Morrey spaces, with focus on harmonic analysis in volume I and generalizations and interpolation of Morrey spaces in volume II. Features Provides a from-scratch' overview of the topic readable by anyone with an understanding of integration theory Suitable for graduate students, masters course students, and researchers in PDE's or Geometry Replete with exercises and examples to aid the reader's understanding
OCLC-licensed vendor bibliographic record.
Keywords: Banach spaces; Harmonic analysis; Differential equations, Partial -- Numerical solutions; Differential equations, Elliptic -- Numerical solutions; Integral operators; MATHEMATICS / General; MATHEMATICS / Differential Equations; MATHEMATICS / Functional Analysis